1979
DOI: 10.1007/bf01963951
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense of crinoids by polyketide sulphates

Abstract: The range of (presumed) polyketide constituents in comatalid crinoids has been extended to include bianthronyls, meso-naphthodianthrones and sulphate esters of various of the polyketides. Several species of fish are deterred from eating food by the inclusion in it of these sulphates at the concentration found in crinoids. Sodium 2-hydroxy-anthraquinone sulphate and anthraquinone-2-suphonate were also active as antifeedants for the species tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…Numerous marine organisms are known to contain toxins (Halstead, 1970(Halstead, , 1978Rideout et al, 1979). Many soft corals (Coelenterata: Alcyonacea) possess an extensive range of unique organic molecules, the majority of which fall into the terpene class of compounds (Tursch et al, 1978;Coll et al, 1980;Coll, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous marine organisms are known to contain toxins (Halstead, 1970(Halstead, , 1978Rideout et al, 1979). Many soft corals (Coelenterata: Alcyonacea) possess an extensive range of unique organic molecules, the majority of which fall into the terpene class of compounds (Tursch et al, 1978;Coll et al, 1980;Coll, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Antifeedant Activity of Ptilometric Acid (2) and Its Sulfate (1) in Fish It has been reported that quinone pigments, especially the sulfate forms, provide a chemical mechanism against predatory fish for some species of crinoids. 9) In this study, ptilometric acid 6-O-sulfate (1) showed concentrationdependent antifeedant activity in fish, but ptilometric acid (2) was ineffective (Table 3). Antifeedant activities of 2-butanoyl-3,6,8-trihydroxy-1,4-naphtoquinone (4) and its sulfate (3) could not be measured because of the small sample size.…”
Section: -Carboxylic Acid 6-o-sulfate)mentioning
confidence: 57%
“…Various reports on the quinone pigments of crinoids have been published. 1) At present, the following four groups of polyketidederived pigments, linear and angular naphthopyrones, [2][3][4] 4-acylanthraquinones, [5][6][7] 3-alkylanthraquinones, 6,8) and diametric bianthrones (bianthraquinones and phenanthroperylenequinones) 9,10) are known to occur in crinoids. Some of the quinone pigments in crinoid are present in sulfate form.…”
mentioning
confidence: 99%
“…However, secondary metabolites such as quinones may also play a role in chemical defense. Hypericin and gymnochromes are well known for their biological activity (8,24), and antifeedant activities against fish have been reported for structurally related anthraquinone pigments from comatulids (27,28). Previous observations on two extant isocrinids, Endoxocrinus parrae and Neocrinus decorus, suggested that stalked crinoids lack chemical defense against fish predation, supporting the hypothesis that restriction of stalked crinoids to deep-water habitats may have resulted from the Mesozoic radiation of durophagous fishes in shallow seas (29).…”
Section: Resultsmentioning
confidence: 77%